Assessment of vascular phenotype using a novel very-high-resolution ultrasound technique in adolescents after aortic coarctation repair and/or stent implantation: relationship to central haemodynamics and left ventricular mass. Issue 21 (27th July 2011) - Sarkola, Taisto; Redington, Andrew N; Slorach, Cameron; Hui, Wei; Bradley, Timothy; Jaeggi, Edgar
Abstract : Objectives: Coarctation of the aorta (CoA) has been associated with abnormal vascular function, increased blood pressure (BP) and premature cardiovascular disease even after a successful intervention. The objective was to determine the severity of residual cardiovascular abnormalities in youths after CoA repair and their relation to regional BP. Design: Cross-sectional study in tertiary healthcare setting. Methods: Thirty-six youths with CoA (age 16±1 years; neonatal surgery only: n=16; surgery and/or stent implantation: n=20) and 37 age-matched controls were prospectively examined using a very-high-resolution vascular ultrasound imaging, echocardiography and applanation tonometry. Results: CoA was associated with increased right arm systolic BP (p<0.001), intima–media thickness (IMT) in the common carotid (p<0.001), right brachial (p<0.05) and radial (p<0.05) arteries and ascending aortic stiffness (p<0.05). Carotid IMT correlated positively with age at first intervention (r=0.36, p<0.05). With left subclavian flap-type repair, left-arm systolic BP (p<0.001) and left brachial (p<0.001), radial (p<0.001) and ulnar (p<0.05) arterial IMTs were all reduced. When adjusted for BP, body mass index, age and gender, only carotid IMT (p<0.001) and left ventricular mass (p=0.013) of stented patients, as well as left-arm arterial IMTs (p<0.01) in subclavian flap-type repair patients, remained different from the controls. The significant associations of the stented patients disappeared after the adjustment for later patient age at intervention (median 8.7 vs 0.03 years, p<0.001). Residual arm–leg BP gradients correlated positively with carotid and brachial IMT. No differences between the CoA patients and the controls were found for arterial adventitial thicknesses, lumen dimensions, thigh systolic BP, abdominal aorta and carotid stiffness and right carotid to radial pulse wave velocity. Conclusion: CoA repair in early childhood is associated with increased preductal arterial IMT, left ventricular mass and ascending aortic stiffness in adolescents. The more pronounced cardiovascular abnormalities after CoA stent implantation are likely related to older patient age at the time of intervention.